Glucose Homeostasis, Pancreatic Endocrine Function, and Outcomes in Advanced Heart Failure - Melenovsky, Vojtech; Benes, Jan; Franekova, Janka; Kovar, Jan; Borlaug, Barry A; Segetova, Marketa; Tura, Andrea; Pelikanova, Tereza (Journal of the American Heart Association, 2017)
BACKGROUND: The mechanisms and relevance of impaired glucose homeostasis in advanced heart failure (HF) are poorly understood. The study goals were to examine glucose regulation, pancreatic endocrine function, and metabolic factors related to prognosis in patients with nondiabetic advanced HF. METHODS AND RESULTS: In total, 140 advanced HF patients without known diabetes mellitus and 21 sex-, age-, and body mass index-matched controls underwent body composition assessment, oral glucose tolerance testing, and measurement of glucose-regulating hormones to model pancreatic β-cell secretory response. Compared with controls, HF patients had similar fasting glucose and insulin levels but higher levels after oral glucose tolerance testing. Insulin secretion was not impaired, but with increasing HF severity, there was a reduction in glucose, insulin, and insulin/glucagon ratio-a signature of starvation. The insulin/C-peptide ratio was decreased in HF, indicating enhanced insulin clearance, and this was correlated with lower cardiac output, hepatic insufficiency, right ventricular dysfunction, and body wasting. After a median of 449 days, 41% of patients experienced an adverse event (death, urgent transplant, or assist device). Increased glucagon and, paradoxically, low fasting plasma glucose displayed the strongest relations to outcome (P=0.01). Patients in the lowest quartile of fasting plasma glucose (3.8-5.1 mmol·L-1, 68-101 mg·dL-1) had 3-times higher event risk than in the top quartile (6.0-7.9 mmol·L-1, 108-142 mg·dL-1; relative risk: 3.05 [95% confidence interval, 1.46-6.77]; P=0.002). CONCLUSIONS: Low fasting plasma glucose and increased glucagon are robust metabolic predictors of adverse events in advanced HF. Pancreatic insulin secretion is preserved in advanced HF, but levels decrease with increasing HF severity due to enhanced insulin clearance that is coupled with right heart failure and cardiac cachexia.
Keywords: homeostáza; Insulin; Male; biologické markery; heart failure; srdeční selhání; inzulin; Risk Factors; Biomarkers; prognóza; Kaplan-Meier Estimate; funkce pravé komory srdeční; krevní glukóza; Ventricular Function, Right; Ventricular Dysfunction, Right; Homeostasis; cachexia; Kaplanův-Meierův odhad; dysfunkce pravé srdeční komory; glukagon; Aged; Case-Control Studies; mužské pohlaví; senioři; glucagon/glucagon‐like peptide; glucose; Severity of Illness Index; Langerhansovy ostrůvky; Cachexia; Time Factors; lidé; ženské pohlaví; studie případů a kontrol; Glucagon; insulin; Heart Failure; Humans; kachexie; časové faktory; rizikové faktory; obesity paradox; Glucose Tolerance Test; Prognosis; Islets of Langerhans; stupeň závažnosti nemoci; Female; Blood Glucose; starvation; lidé středního věku; glukózový toleranční test; right ventricular dysfunction; Middle Aged; metabolism